2013
DOI: 10.4103/0976-500x.110894
|View full text |Cite
|
Sign up to set email alerts
|

Scientific evaluation of the scholarly publications

Abstract: Worthiness of any scientific journal is measured by the quality of the articles published in it. The Impact factor (IF) is one popular tool which analyses the quality of journal in terms of citations received by its published articles. It is usually assumed that journals with high IF carry meaningful, prominent, and quality research. Since IF does not assess a single contribution but the whole journal, the evaluation of research authors should not be influenced by the IF of the journal. The h index, g index, m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0
7

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(33 citation statements)
references
References 11 publications
1
25
0
7
Order By: Relevance
“…The Google h-index and the 5-year impact factor have both grown in the past 2 years (Bond & Buntins, 2018); however citations alone are not enough to measure a journal's quality . Using impact factors to evaluate educational research is problematic due to bias, skewing of metrics, editorial policies, and methodological preferences (Lavie, 2009;Ouimet, Bedard, & Gelineau, 2011;Saxena, Thawani, Chakarbarty, & Gharpure, 2013;Staller, 2017), therefore this research seeks to explore AJET's impact and support of scholars and scholarship beyond metrics alone (West & Rich, 2012).…”
Section: Ajet In Previous Bibliographic Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…The Google h-index and the 5-year impact factor have both grown in the past 2 years (Bond & Buntins, 2018); however citations alone are not enough to measure a journal's quality . Using impact factors to evaluate educational research is problematic due to bias, skewing of metrics, editorial policies, and methodological preferences (Lavie, 2009;Ouimet, Bedard, & Gelineau, 2011;Saxena, Thawani, Chakarbarty, & Gharpure, 2013;Staller, 2017), therefore this research seeks to explore AJET's impact and support of scholars and scholarship beyond metrics alone (West & Rich, 2012).…”
Section: Ajet In Previous Bibliographic Studiesmentioning
confidence: 99%
“…Whilst citation analyses are "commonly used to explore the intellectual structure of a given discipline" (Liu & Wang, 2005, p. 308), interpreting educational research quality using impact factors alone is problematic (Lavie, 2009;Ouimet, et al, 2011;Saxena, et al, 2013;Staller, 2017), particularly given the issues in assessing research quality in Australia (e.g., Smith, 2014). Therefore, in order to explore how AJET has furthered scholarship in the field (research question two), an analysis of AJET's rigour, impact and prestige was undertaken, following the framework by West & Rich (2012).…”
Section: Evaluation Of Rigour Impact and Prestigementioning
confidence: 99%
“…Interpreting educational research quality by using impact factors has been identified as particularly problematic, due to a range of factors including skewing of metrics, editorial policy, the small number of journals indexed in the ISI (Lavie, 2009;Saxena, Thawani, Chakrabarty, & Gharpure, 2013;Staller, 2017;West & Rich, 2012), and author epistemological or methodological preferences (Ouimet, Bedard, & Gelineau, 2011). Therefore, the results of this analysis should be viewed as one measure of AJET's quality.…”
Section: Journal Metric Analysismentioning
confidence: 99%
“…Indeed, many additional factors may bias paper citation rates. These may include eminence of the author or institution [12,18]; tendency to self-citation by some authors [14]; increased citing of authors published in the same country or language [7,11]; and research with positive results rather than no difference or negative results [3,4]. Probably most important among these other factors is the prominence of the journal in which the paper is published.…”
Section: Discussionmentioning
confidence: 99%